SPERM COLLECTION BY MICRO TESE METHOD IN PATIENTS WITH NONOBSTRUCTIVE AZOOSPERMIA AND SOME RELATED FACTORS (Vietnam Journal of Community Medicine, 2022)
Question: Microdissection testicular sperm extraction (micro tese) is a highly effectivemethod of sperm collection with a low risk of secondary testicular damage. Objectives: Toevaluate the sperm collection rate by microtese method in patients with nonobstructiveazoospermia (NOA) and some related factors. Subjects and research methods: 132NOA patients were micro-tese made at the Military Clinical Embryo Institute - VietnamMilitary Medical University from 5/2017 to 12/2019. Results: The sperm collectionrate was 40.15%. There was no association between age, BMI, duration of infertility,AZF with sperm collection rate. There was a relationship between testicular volume,hormone concentration, histopathology, and sperm collection rate. The cut-off point ofthe right and left testicular volumes were 5.5mL, with a sensitivity of 86.3% and 84.3%,specificity of 50.6% and 51.9%, and a curve area of 0.707, respectively and 0.676 (p
Keywords: Microdissection testicular sperm extraction (micro tese); Non-obstructive azoospermia; sperm collection.